(untitled) (Community Based Medical Journal, 2015)
Traumatic abdominal wall hernia is a rare condition that can follow any blunt trauma. Associated intra-abdominal injuries are infrequent. In this case report, a middle aged man diagnosed as abdominal wall hernia following fall from height, surprisingly without any other injury. Aim of this report is to augment the knowledge of traumatic abdominal wall hernia, its diagnosis and proper treatment. CBMJ 2015 July: Vol. 04 No. 02 P: 58-61